Internet-based cognitive behavioral therapy for improving health-related quality of life in patients with endometriosis: study protocol for a randomized controlled trial - Schubert, Kathrin; Lohse, Johanna; Kalder, Matthias; Ziller, Volker; Weise, Cornelia (Trials, 2022)
Background: The trial investigates the efficacy of internet-based cognitive behavioral therapy (iCBT) in improving health-related QoL in patients with endometriosis, which is a chronic gynecological condition affecting up to 15% of people with female-assigned reproductive organs. Endometriosis is stress-related and comes with various physical symptoms such as pelvic pain and infertility. It has a substantial impact on health-related quality of life (QoL), and mind-body interventions seem promising in reducing the psychological burden. Methods: This is a monocentric randomized-controlled trial recruiting 120 patients with endometriosis. The intervention consists of eight iCBT modules focusing on psychoeducation, cognitive restructuring, pacing, and emotion regulation. Participants will receive written feedback from a trained therapist weekly. The comparator is a waitlist control group. All participants will be followed up 3 months after the intervention, and the intervention group will additionally be followed up 12 months after the intervention. Trial participants will not be blinded to the allocated trial arm. Primary outcome measures are endometriosis-related QoL, pain, and pain-related disability. Secondary outcomes include coping, illness representations, and psychological flexibility. Statistical analyses will be performed following intention-to-treat principles. Discussion: This randomized-controlled trial is the first trial to test the efficacy of iCBT for improving endometriosis-related QoL. Potential predictor variables and key mechanisms in treatment will be investigated to enable further progression in medical and psychological care for patients with endometriosis. Trial registration: ClinicalTrials.gov, NCT05098444 Registered on October 28, 2021
CRIS-Team Scopus Importer:2024-03-27
Keywords: CBT; Chronic pelvic pain; Endometriosis; Internet-based intervention; RCT; Women’s health